Writing Final Year Project Report in English: Problems, Motivating and Hindering Factors among UTeM Final Year Engineering Students - Noor Baiduri, Abd Halim; Nordayana Izyan, Ahmad Ahsan; Fudhail, Abdul Munir (CCSE, 2012)
In this study, the scope is confined to final year engineering students where the aim of the paper is primarily to look at the motivating and hindering factors for these students to choose the English language when preparing for their final year engineering project reports. These students are from four engineering faculties in Universiti Teknikal Malaysia Melaka (UTeM). A quantitative approach was employed in this study. The study found that the tasks of understanding, selecting and integrating resources to their projects , not to forget the problem of composing the paper which is always influenced by their first language, are always the hindering factors to students. Many students did not begin to learn how to approach this task until they were in the process of writing the report. Meanwhile, students are mostly motivated to write report in English due to the dominantly available resources relevant to their project topic written in English.